Figures of Southeast Asian modernity - Barker, Joshua 1967-; Harms, Erik (Anthropologist); Lindquist, Johan (University of Hawaiʻi Press, 2014)
Brings together the fieldwork of over eighty scholars and covers the nine major countries of the region: Burma (Myanmar), Cambodia, Indonesia, Laos, Malaysia, the Philippines, Singapore, Thailand, and Vietnam. Each section begins with an introduction by a country editor followed by short essays offering vivid and intimate portraits set against the background of contemporary Southeast Asia.